Habilidades cognitivas y su impacto en el desarrollo de la estimulación sensorial del CNH - Robelli Cabezas, Anaís Maite (2020)
The objective of the research is to facilitate knowledge in the early stimulation sensory from 0 months to 3 years of age of the CNH (GROWING WITH OUR SONS) of the First of December sector of the Clemente Baquerizo parish of the city of Babahoyo, research that shows the interaction between parents and children and educators for the development, skills and abilities of learning. It is important that parents know the different exercises to develop the senses and stimulate them with different activities such as music for the development of hearing, the materials that we find in our environment for tactile development, elements that we have such as food for develop smell and sense of taste. The implemented methodology begins with a census to obtain the necessary information from each family, and to achieve a learning relationship with parents and children, because the basic characteristics such as the need for each family's learning are recognized; the confidence and development to be able to carry out the activities in class and meet the requirements of the educator.